(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Thematic dictionaries serve as essential tools for language learning, translation, and specialized communication. This article explores the lexicographic principles involved in compiling thematic dictionaries in English and Uzbek. It discusses criteria for word selection, categorization, and the challenges of maintaining semantic accuracy and cultural relevance. A comparative analysis highlights the differences in thematic structuring and translation difficulties between the two languages. The study also examines the role of digital tools and AI in modern dictionary-making, offering recommendations for improving bilingual thematic lexicography. The findings contribute to the development of user-friendly and linguistically accurate dictionaries, benefiting linguists, educators, and translators.